Coping with Stress by Members of the Domestic Church Community - Opalach, Cezary Wojciech (Studia Warmińskie, 2024)
This article presents the results of an empirical verification of the hypothesis that members of the Domestic Church (DK) community present more effective styles of coping with stressful situations. The research was conducted on a group of 30 married couples belonging and not belonging to this community, based on the Coping with Stress Questionnaire (CISS), by Norman S. Endler and James D. A. Parker. They confirmed the hypothesis and proved that DK members most often use a task-oriented strategy and least often an avoidance-oriented strategy, in the form of involvement in substitute activities. The primary source of the obtained data seems to be DK membership, which allows to use prayer and marital dialogue, high level of religiosity, communication competence and life wisdom in the fight against stress, even with a lower level of education than in the control group. However, it cannot be ruled out that, with regard to some of these factors, DK membership only plays a mediating role and that the correlations obtained are most correlated with intelligence and personality. Further empirical research is needed to conclusively resolve these doubts.